Low loss splicing methods of photonic crystal fibre and single mode fibre - Ng, Jun Yang (2013)
Photonic Crystal Fibres (PCFs) are increasing being used applications like fibre lasers and optic fibre communication systems. The main problem with using PCF is due to the high loss associated when spliced with conventional single mode fibres. This project explores the possible methods of splicing PCF to SMF using standard laboratory equipment. [2nd Award]